If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(-3 + -2x) + -5 = 0 (-3 * -1 + -2x * -1) + -5 = 0 (3 + 2x) + -5 = 0 Reorder the terms: 3 + -5 + 2x = 0 Combine like terms: 3 + -5 = -2 -2 + 2x = 0 Solving -2 + 2x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + 2x = 0 + 2 Combine like terms: -2 + 2 = 0 0 + 2x = 0 + 2 2x = 0 + 2 Combine like terms: 0 + 2 = 2 2x = 2 Divide each side by '2'. x = 1 Simplifying x = 1
| -35-14x=21-16x | | 10x^2-16x-6=0 | | 5x+17y=91 | | (-2i)(-8i)(2)= | | 4-6x=x+11 | | -56+24=22x+22 | | 15=2(5m+10)+3(5-4m) | | n-17=-18 | | -10(-9+x)=190 | | -116-14=-7x+213 | | (2x^2)-7y^2=-13 | | 5(5n+9)+2= | | b+42=19 | | -129+20x=12x+207 | | 11m=-110 | | 5a-4a+2b-4= | | -16x=272 | | 6(v+4)-2v=2(2v+3)-9 | | X-10y=12 | | -177+5x=299+19x | | b-9=3 | | 3(x-2)=3(x+4) | | 3(7p-1)-6= | | -22x-51=61-18x | | n-16=3 | | -6=k+5 | | 9x^2+7x-2= | | cos(x)=cos(3x) | | 6+6(2t-1)=36 | | -149+13x=20x+131 | | 32=-2m | | 32=-2 |